Vegetarian Epidemiology: Review and Discussion of Findings from Geographically Diverse Cohorts. (15th November 2019) - Orlich, Michael J; Chiu, Tina H T; Dhillon, Preet K; Key, Timothy J; Fraser, Gary E; Shridhar, Krithiga; Agrawal, Sutapa; Kinra, Sanjay
ABSTRACT: Epidemiologic cohort studies enrolling a large percentage of vegetarians have been highly informative regarding the nutritional adequacy and possible health effects of vegetarian diets. The 2 largest such cohorts are the European Prospective Investigation into Cancer and Nutrition–Oxford (EPIC-Oxford) and the Adventist Health Study–2 (AHS-2). These cohorts are described and their findings discussed, including a discussion of where findings appear to diverge. Although such studies from North America and the United Kingdom have been important, the large majority of the world's vegetarians live in other regions, particularly in Asia. Findings from recent cohort studies of vegetarians in East and South Asia are reviewed, particularly the Tzu Chi Health Study and Indian Migration Study. Important considerations for the study of the health of vegetarians in Asia are discussed. Vegetarian diets vary substantially, as may associated health outcomes. Cohort studies remain an important tool to better characterize the health of vegetarian populations around the globe.